Constitutionality Of Independent Government Regulations (PP) In Indonesia - Ahla Nurus Saada (Manunggal Halim Jaya, 2026)
This study examines the constitutionality of independent Government Regulations (PP) within the Indonesian legal system. Independent Government Regulations (PP) are regulations issued by the President without an explicit delegation of authority from a law, but based on the attribution of authority under Article 5 (2) of the 1945 Constitution. This phenomenon has sparked debate regarding its compatibility with the principles of the rule of law and the principle of legality. Using a normative legal approach, this study analyzes legislation, Supreme Court decisions, and the opinions of constitutional law experts through a literature review. The research findings indicate that independent Government Regulations (PP) are constitutional as long as their issuance is based on the President’s delegated authority and does not conflict with laws or the 1945 Constitution. However, their existence must remain subject to oversight through the Supreme Court’s judicial review mechanism to ensure their conformity with the hierarchy of legislation and the principle of legality. These findings underscore the importance of legal clarity in the formulation of Government Regulations to prevent legal uncertainty and potential abuse of authority, while simultaneously strengthening the constitutional system and regulatory framework in Indonesia.